1984
DOI: 10.1139/v84-350
|View full text |Cite
|
Sign up to set email alerts
|

The effect of heavy-atom solvents on the photooxidation of anthracene

Abstract: Photoirradiation of anthracene in benzene in the presence of oxygen gave predominantly a photodimer of anthracene, and very little oxidation product. Similar irradiation of anthracene in bromobenzene, however, produced 9,10-anthraquinone in high yield. The yield of anthraquinone increased in the presence of a heavy-atom solvent such as bromobenzene, p-dibromobenzene, 1,3,5-tribromobenzene, 1-bromopropane, and dibromomethane in proportion to the sum of squares of the spin–orbit coupling parameter ζ of the solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…To test the feasibility of this approach, we initially explored converting ethyl 2‐(anthracen‐9‐yl)acetate 2 a into anthraquinone 4 a with the visible light‐induced photooxidation process . The photooxidation mechanism of acenes was proposed to go through a photoinduced electron transfer redox process and radical coupling with superoxide . An alternative reaction pathway involves formation of singlet oxygen ( 1 O 2 ) by the sensitizer, which reacts with acenes to afford endoperoxides.…”
Section: Methodsmentioning
confidence: 99%
“…To test the feasibility of this approach, we initially explored converting ethyl 2‐(anthracen‐9‐yl)acetate 2 a into anthraquinone 4 a with the visible light‐induced photooxidation process . The photooxidation mechanism of acenes was proposed to go through a photoinduced electron transfer redox process and radical coupling with superoxide . An alternative reaction pathway involves formation of singlet oxygen ( 1 O 2 ) by the sensitizer, which reacts with acenes to afford endoperoxides.…”
Section: Methodsmentioning
confidence: 99%
“…There are many possible mechanisms for the photodegradation of PAHs. Toshima et al 35 incorporated earlier work into a mechanistic study of anthracene which demonstrated the action of both free radical and singlet oxygen mechanisms in solution photooxidation reactions. Their results have been supported by others.…”
Section: Anthracene Photochemistrymentioning
confidence: 99%
“…The broad emission band with the characteristic vibrionic structure is assigned to the fluorescenceo f the dpa ligand in the Eu III coordination polymer.T his spectrum agrees with that of the bpa ligand ( Figure S4). The peaks in the narrowb ands are observed at 579, 594,6 13, 655, and 700 nm, which are assignedt ot he 5…”
mentioning
confidence: 92%
“…The anthracene reacts with singlet oxygen ( 1 O 2 )g enerated by energy transfer from triplet anthracene ( 3 Ant) to triplet oxygen ( 3 O 2 ). [5] The stacked coordination polymer with hfaa nd aromatic bridged ligandsa lso induced CH-F interactions. The CH-F interactions promote the formation of tribo-excited states.…”
mentioning
confidence: 99%